2017
DOI: 10.2174/1389450116666150223162737
|View full text |Cite
|
Sign up to set email alerts
|

Primary Cilia in Tumor Biology: The Primary Cilium as a Therapeutic Target in Cholangiocarcinoma

Abstract: Cilia are microtubule-based organelles, which are ubiquitously expressed in epithelial cells. Cholangiocytes, the epithelial cells lining the biliary tree, have primary cilia extending from their apical plasma membrane into the ductal lumen, where the cilia function as multisensory organelles transducing environmental cues into the cell interior. The decrease or loss of primary cilia has been described in several malignancies, including cholangiocarcinoma, suggesting that the loss of cilia is a common occurren… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
34
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
5
2

Relationship

3
4

Authors

Journals

citations
Cited by 34 publications
(38 citation statements)
references
References 67 publications
(73 reference statements)
1
34
0
Order By: Relevance
“…Mature cholangiocytes have a single primary cilium extending from the apical membrane [26], which in addition to other physiological roles, functions as a structural cell cycle checkpoint. Thus, its loss or shortening induces proliferation in several cholangiopathies [26].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Mature cholangiocytes have a single primary cilium extending from the apical membrane [26], which in addition to other physiological roles, functions as a structural cell cycle checkpoint. Thus, its loss or shortening induces proliferation in several cholangiopathies [26].…”
Section: Discussionmentioning
confidence: 99%
“…Thus, its loss or shortening induces proliferation in several cholangiopathies [26]. Human CCA cells show loss or decreased primary cilium length, which is dependent on the overexpression of HDAC6 that de-acetylates the cilium scaffold protein α-tubulin [19, 26]. SOX17 overexpression induced the downregulation of HDAC6 together with the restoration of primary cilium structure and size, indicating improved cell polarity and differentiation.…”
Section: Discussionmentioning
confidence: 99%
“…The primary cilium is a sensory organelle expressed in almost every cell of the body, including cholangiocytes [58,59]. Several studies have reported that primary cilia can serve as antennae, which have mechanical and chemical sensory capabilities to communicate with the extracellular environment.…”
Section: Ciliary Assemblymentioning
confidence: 99%
“…Disorders linked with genetic mutations in ciliary proteins often lead to abnormality in cilia formation. Ciliary dysfunction has been associated with intellectual disabilities, Bardet-Biedl syndrome, polycystic kidney disease, obesity, oral facial syndrome, cancer, and others [58,60,61]. Specifically, decreased or distorted primary cilia in cholangiocytes have important clinical implications and are associated with many biliary diseases, including CCA [62,63].…”
Section: Ciliary Assemblymentioning
confidence: 99%
“…many new signaling pathways related to the primary cilium have been identified, and novel functions of the primary cilium, such as responding to microgravity, electromagnetic fields, nitric oxide and mediating carcinogenesis, have been confirmed, greatly augmenting the importance of the primary cilium (Gradilone, Pisarello, & LaRusso, 2017;Moser et al, 2013;Saternos & Aboualaiwi, 2018;Shi, Xie, et al, 2017;Yan et al, 2015). Here, we summarize our current understanding of new discoveries about the functional role of the primary cilium and novel insight into cellular signaling by the primary cilium in bone disease and cancer.…”
mentioning
confidence: 99%